2008
DOI: 10.1016/j.jue.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Has SARS infected the property market? Evidence from Hong Kong

Abstract: This paper uses the 2003 Hong Kong Severe Acute Respiratory Syndrome (SARS) epidemic as a natural experiment to investigate how housing markets react to extreme events. A panel data set of large-scale housing complexes (estates) is used to exploit the cross-sectional variation in the spread of SARS to estimate the effect of the disease on real estate prices and sales. SARS risk is measured by: (1) the estate-level SARS infection rate, (2) news reports, and (3) government announcements of infections. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 20 publications
10
91
0
1
Order By: Relevance
“…The S.A.R.S. epidemic also involved a clear change in investors' risk level (Wong, 2008). Economists have long observed that societal responses to health risks tend to be extreme and inconsistent (Viscusi, 1989(Viscusi, , 1990.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The S.A.R.S. epidemic also involved a clear change in investors' risk level (Wong, 2008). Economists have long observed that societal responses to health risks tend to be extreme and inconsistent (Viscusi, 1989(Viscusi, , 1990.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Market integration related studies have looked at specific events such as financial crises (Chevapatrakul & Tee, 2014;Răileanu-Szeles & Albu, 2015), the European Union (or Euro monetary union) implementation (Christiansen, 2014;Ogrokhina, 2015), political crises (Frijns, Tourani-Rad & Indriawan, 2012), and air crashes (Ho, Qiu & Tang, 2013), but it remains an open question as to whether these unexpected crises will weaken or strengthen the long-run relationship in aggregate stock price indices within an integrated market. For example, Yu, Fung, and Tam (2010) show that the equity market integration process of A.S.E.A.N.+3 (Association of Southeast Asian Nations) countries picked up in 2007-2008, while Wang (2014 identifies that the global financial crisis has strengthened the linkages among stock markets in East Asia, signifying that time-varying long-run relationships exist among these countries. Hemche, Jawadi, Maliki, and Cheffou (2016) find a substantial increase in dynamic correlations following the recent subprime crisis for most markets under consideration with regard to the U.S. market.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that other extreme events, such as Hurricane Floyd (Bin and Polasky, 2004) and 9/11 attack (Abadie and Dermisi, 2008), have significantly affected house prices. However, Wong (2008) found no evidence of excessive price reactions to the 2003 Severe Acute Respiratory Syndrome (SARS) epidemic in Hong Kong.…”
Section: Fna and Nuclear Industry Development In Chinamentioning
confidence: 99%
“…Thus, sellers' loss aversion drives the phenomenon of low transactions during the market downturn. The approach is then supported by a stream of housing literature (Engelhardt 2003;Wong 2008). The work of Ong et al (2008) distinguishes loss aversion from disposition effect using Singapore housing transaction data including both foreclosure sales and non-foreclosure sales in Singapore condominium market.…”
Section: The Related Literaturementioning
confidence: 99%